Medicinal chemistry strategies in combating antibiotic resistance - Coxon, Geoffrey (Henry Stewart Talks, 2009)
Overview of the drug discovery process, Mechanisms of antibiotic action and resistance, Modification of the antibiotic pharmacophore, Modification of the target structure, Targeting existing therapy and resistance mechanisms, Overcoming modification in the target structure, Considerations and methods in the discovery of new antibiotics, Genomic based approaches, Lead discovery approaches, Fragment based drug discovery, Modelling: ligand and structure known approach, Modelling: structure known but ligand unknown approach, Modelling: ligand known but structure unknown, Whole cell (empirical) based approaches, Selection of chemical starting points